Global Tendencies in University Development and Transformation of Russian Education Policy - M. M. Lebedeva; O. N. Barabanov (Vestnik MGIMO-Universiteta)
The article reviews evolution of modern university, which has acquired a new political function and a reaction to this development of education policy in Russia. Authors argue that the strategy of catch-up development might be successful in case of Russian higher education system and its potential on the global competitive education market.